Comparing the efficacy of Silastic and gloved‐Merocel middle meatal spacers for functional endoscopic sinus surgery: a randomized controlled trial. Issue 8 (30th March 2018) - Manji, Jamil; Habib, Al‐Rahim R.; Macias‐Valle, Luis; Finkelstein, Andres; Alsaleh, Saad; Dadgostar, Anali; Al‐Asousi, Fahad; Okpaleke, Christopher; Javer, Amin R.
Abstract : Background: Spacers are inserted into the middle meatal space (MMS) following functional endoscopic sinus surgery (FESS) to prevent lateralization of the middle turbinate, scarring, and synechiae. Our objective was to determine if the incidence of postoperative synechiae, facial pain/discomfort, pain during spacer removal, scarring, and discharge differed between nasal cavities receiving Silastic or gloved‐Merocel (GM) spacers following FESS. Methods: A double‐blind, randomized controlled trial (RCT) was conducted in adults requiring bilateral FESS for chronic rhinosinusitis (CRS) ± nasal polyposis. Participants served as their own controls, with each subject receiving both a Silastic and GM spacer. Spacers were inserted into the MMS during FESS and left in situ for 6 days. Participants were reviewed at 6 days, 5 weeks, and 12 weeks postoperatively. The presence of synechiae and scarring were evaluated endoscopically. Inflammation, discharge, and pain during spacer removal were assessed using a visual analogue scale (VAS). Results: Forty‐eight participants (96 nasal cavities) were recruited. Preoperatively, Lund‐Mackay computed tomography (CT) scores were similar between Silastic‐treated and GM‐treated cavities (6.38 ± 2.35 vs 6.18 ± 2.17). The incidence of synechiae and scarring did not differ significantly between spacers up to 12 weeks postoperatively. Pain during spacer removal was significantly greater for Silastic than GM spacers (2.13 ± 1.34 vs 1.51 ± 1.23, p = 0.020). Facial pain prior to removal and extent of discharge did not differ significantly between spacers. Conclusion: Following FESS, patients report less pain during removal of GM than Silastic spacers. However, the likelihood of synechiae and scarring did not differ between either of the spacers.